Beyond Tariffs and Quotas: Why Do African Manufacturers Not Export More? - Clarke, George R. G. (2012)
Africa's export performance has been extremely poor in recent years. Its share of world exports has declined and most countries are highly dependent on a narrow range of primary commodities for export earnings. This paper looks at factors that affect the export performance of manufacturing enterprises in eight African countries. In addition to enterprise characteristics (e.g., size, ownership, and education of the manager), policy-related variables also affect exporting. Manufacturing enterprises are less likely to export in countries with restrictive trade and customs regulations and poor customs administration.